Study on Customer’s Perception towards a Digital Marketing Company - et. al., Dr. Sridevi K.B, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital marketing is also known as Internet (or) Online advertising, it is a form of marketing and advertising that involves sending promotional marketing messages to customers through the Internet. Email marketing, search engine marketing (SEM), Social media marketing, a variety of display ads (including online banner ads), and smartphone advertising are all part of it. Internet advertising, like other types of advertising, often includes both a publisher and an advertiser. The publisher incorporates ads into its online material, and the advertiser produces the advertisements to be shown on the publisher's content. Advertising agencies who help to create and position ad copy, an ad server that produces the ad and records statistics, and advertising associates that do in-dependent promotional work for the advertising company all are possible participants. And in this study the Perception of the customer is to analyse that how they satisfied about the work of the company that they designed the digital marketing product for an organization or customer for digital advertising purpose and for promotion purpose to market their product or brand to advertise on the market to attract customers. From this study the effectiveness of the digital marketing is to analyse, and the effectiveness & customer’s satisfaction level are to be analysed among the phoenix digital marketing company’s customer. The data are to be collected by using Google form and various kind of analysis is to be used and analysed by using SPSS Software.